Studi Pemisahan Bitumen Asbuton Menggunakan Proses Flotasi - Aldiyansyah Aldiyansyah (LP3M Universitas Muhammadiyah Kendari, 2022)
Buton Island, located in Southeast Sulawesi, has natural asphalt reserves, namely Buton asphalt, which spread from the bay to Sampawa to of Lawele. The advantages of Buton asphalt include higher pavement stability when compared to oil asphalt and are more weather resistant and can save pavement thickness by up to 22%. This research is a study conducted to separate Asbuton bitumen from its impurity minerals using the flotation method. The purpose of this study is to increase the levels of bitumen and also recovery. From the results of the experiment The variation in pH carried out showed an optimum increase in bitumen content at pH 7 using kerosene collectors, namely concentrations of 38.7% with 85.81%, the collector dose showed an increase in bitumen levels at a doses of 150 gr / ton, 34, 4% with the recovery of 52.54%. and a solid percent variation showed an increase in bitumen levels, which was 20% percent solid with 35.4% content with the recovery of 72.95%.